The size of lymph nodes in the neck on sonograms as a radiologic criterion for metastasis: how reliable is it? - van den Brekel, M W; Castelijns, J A; Snow, G B (American Journal of Neuroradiology, 1998)
PURPOSE A definition of cut-off points for nodal size is essential to determine whether cervical lymph nodes are metastatic or not. Because the currently used size criteria are defined for random populations of patients with head and neck cancer, we set out to study whether these criteria are optimal for patients without palpable metastases in different levels of the neck We defined optimal size criteria for sonography by calculating the sensitivity and specificity of different size cut-off points.METHODS We compared the sensitivity and specificity of different size cut-off points as measured on sonograms for various levels in the neck in a series of 117 patients with and 131 patients without palpable neck metastases.RESULTS A minimum axial diameter of 7 mm for level II and 6 mm for the rest of the neck revealed the optimal compromise between sensitivity and specificity in necks without palpable metastases. For all necks together (with and without palpable metastases), the criteria were 1 to 2 mm larger.CONCLUSION Our findings indicate that the current sonographic size criteria used for random patient populations are not optimal for necks without palpable metastases, nor can the same cut-off points be used for all levels in the neck.